Effect of pre-strain on cyclic plastic behaviour of 7050-T6 aluminium alloy - Branco, R. (2019)
This paper aims at studying the pre-strain effect on cyclic plastic behaviour of the 7050-T6 aluminium alloy. In order to meet this goal, different series of tests with various pre-strain histories are performed under fully-reversed strain-controlled conditions. In a second stage, fracture surfaces are examined by scanning electron microscopy to identify the main fracture damage micro-mechanisms associated with the pre-strain scenarios. Overall, the results show that higher tensile pre-strain levels lead to lower fatigue lives. This reduction of the fatigue life expectancy tends to increase for higher cyclic strain amplitudes.